Editorial - Vieira, Wilson; Cepêda, Vera Alves; de Malta, Maria Mello (Cadernos do Desenvolvimento, 2023)
Editorial. Cadernos do Desenvolvimento, Centro Celso Furtado, Rio de Janeiro, v. 17, n. 32, p. 8-9, maio-ago. 2022.